2022
DOI: 10.1021/acsaem.2c00657
|View full text |Cite
|
Sign up to set email alerts
|

Stoichiometric Effect of Sb2Te3 Thin Film on Thermoelectric Property

Abstract: Properly selecting electrode materials for antimony telluride (Sb 2 Te 3 ) thermoelectric (TE) thin film enhances the power factor. This study analyzed the compositional variation and measured the TE properties of pristine antimony telluride (Sb 2 Te 3 ), Ni/Sb 2 Te 3 / Ni, and Cu/Sb 2 Te 3 /Cu thin films that were aged to simulate real applications. The rapid diffusion of Cu in the Cu/Sb 2 Te 3 /Cu film resulted in the massive growth of the CuTe intermetallic compound (IMC), which led to Te deficiency. Te def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Also, the antisite defects of the thermoelectric materials are responsible for their thermoelectric properties. Sun et al proposed a defect reaction model that explains the important role of Sb 2 O 3 in the Sb 2 Te 3 system, which reduces the amount of Sb and increases the excess Te to form the Te Sb · antisite defects . Furthermore, the electronegativity of Bi (2.02) and Te (2.1) is similar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the antisite defects of the thermoelectric materials are responsible for their thermoelectric properties. Sun et al proposed a defect reaction model that explains the important role of Sb 2 O 3 in the Sb 2 Te 3 system, which reduces the amount of Sb and increases the excess Te to form the Te Sb · antisite defects . Furthermore, the electronegativity of Bi (2.02) and Te (2.1) is similar.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that the thermoelectric properties worsened after long-term aging. The decreased thermoelectric performance may be due to grain coarsening and the annihilation of crystal defects after the aging process. ,, Although the PF of the Cu_30 sample decreased after aging, the degradation was much less than that of the pristine Bi 2 Te 3 after aging for 30 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the diffusion of Cu into the Sb lattice site along the c-axis results in the creation of antisite defects by producing more Sb 2 O 3 up to that concentration. 40 Beyond 0.4 mM, the intensity of the Sb-O vibrations decreases as Cu-rich phase formation takes place in the deposited lms. These results are consistent with XRD results as discussed earlier.…”
Section: Raman Analysismentioning
confidence: 98%
“…On the other hand, the rapid diffusion of Cu into SbTe and the formation of Sb 2 O 3 may have a considerable effect on the Seebeck coefficient and power factor. 40 The surface Sb 2 O 3 limits the formation of Sb Te antisite defects, and more Cu diffusion leads to the Te sublimation by forming CuSbTe and creates excess V Te , which contributes two electron carriers. Thereby, all the samples behave as n-type, and show a high negative Seebeck coefficient.…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%